Analysis of Factors Influencing Impulsive Buying at Night from a Gender Perspective - Listia Nurjanah; Veren Apriana Jolie (Dinasti Review, 2025)
This study aims to analyze the influence of the Functionality Component and Psychological Component on Online Impulsive Buying, both directly and indirectly through the mediating variables of Attitudinal Loyalty and Self-Control. This research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) as the analysis technique. The results show that both the Functionality Component and Psychological Component have a significant effect on Attitudinal Loyalty, while only the Functionality Component shows an effect on Self-Control, although the effect is not significant. Additionally, Attitudinal Loyalty has a significant positive influence on Online Impulsive Buying, while Self-Control has a significant negative influence on such behavior. These findings indicate that consumers’ attitudinal loyalty plays an important role in driving online impulsive buying behavior, whereas self-control is not sufficiently effective as a deterrent. This study contributes theoretically to the development of consumer behavior models and offers practical implications for digital marketing strategies aiming to maximize customer loyalty to encourage purchase decisions.